Incudostapedial joint dislocation with conductive hearing loss: a case report - Dhingra, Preeti; Pusalkar, Ashutosh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Trauma to the ossicular chain is a common complication of fracture temporal bone, ossicular dislocation being more common than ossicular fracture. Most commonly affected ossicles are the incus and malleus, stapes being relatively more stable. The most common injury is the incudostapedial joint dislocation. We are presenting a case of unilateral conductive hearing loss in a patient with the pre operative diagnosis of otosclerosis, which intra-operative turned out to be incudostapedial joint dislocation with malleus fixation, successfully reconstructed with partial titanium implant.